FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PT. PANCA PRIMA MINING SAMARINDA - Setiawan, Verry (EKONOMIA, 2013)
VERRY SETIAWAN, Factors - Factors Affecting Employee Performance PT . Panca Prima Samarinda Mining under the guidance of (Mother Theresia Militina and Father Heriyanto).The background of this research aspects of internal motivation and external motivation . The research data was obtained from the results of the method of the respondents (questionnaire) , and the relevant results of other studies with the object under study , in this case secondary data from company PT . Panca Prima Mining Samarinda. The analysis model used in this study is multiple linear regression analysis using SPSS 20.The hypothesis of this paper is the internal motivation and external motivation have a significant effect on employee performance . Internal motivation dominant influence on employee performance .This study aims to determine the effect of motivation on employee performance and determine the dominant variables affecting employee performance . Sampling technique in this study using the population census are all employees of PT . Panca Prima Samarinda Mining numbered 38 people . The analysis used in this study is the multiple linear regression , hypothesis testing F test and t test .Based on the analysis of the authors of the test results is the F test F count > F table is 11.995 > 3.32 alpha 5 % and Adjusted strengthened determination test ( R2 ) of 0.373 means that internal motivation variable ( X1 ) and external motivation ( X2 ) significantly 37 , 3 % of the employee's performance variable ( Y ) is also reinforced with a significant level of 0.000, which means that internal motivation variable ( X1 ) and external motivation ( X2 ) has a significant influence simultaneously on employee performance variable ( Y ) .Of the t test can be obtained t count > t table means employee performance variable ( Y ) has a significant effect on the rate of 0.001 significant internal motivation variable ( X1 ) and external motivation ( X2 ) X1 t count > t table ( 3.705 > 2.028 ) with a beta coefficient of 0.483 or 48.3% thus declared to have significant impact on internal motivation variable ( X1 ) and external motivation ( X2 ) t count > t table ( 3.393 > 2.028 ) and a significant level of 0.002 so that external motivation variables ( X2 ) has a significant influence on employee performance variable ( Y ) is reinforced with a beta coefficient of 0.0442 or by 44.2 % . Then the dominant variables affect the performance of the employee ( Y ) is the internal motivation (X1) , internal motivation variable (X1) has the greatest value to the value of 0.483 % and a significant level of 0.001 . Then Hypothesis H1 and H2 hypothesis is accepted .